Tafsîr Maudhû’î Perspektif Ibn Al-Qayyim: Studi Komparatif Al-Tafsîr Al-Qayyim, Badâ’i’ Al-Tafsîr, Dan Al-Dhau’ Al-Munir ‘alâ Al-Tafsîr - Maya, Rahendra; Alfarisi, Muhammad Fadilah; Rokim, Syaeful; Bulloh, Muhammad Naji (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
This research article aims to thematically describe Ibnu Al-Qayyim’s interpretation of the verses and lettres of the Qur’an (maudhu’i) and analyze it from his works. This research uses a qualitative-comparative method with a library study approach and uses a thematic interpretation method (maudhu’i) which is descriptive in nature with data collection techniques using literature and documentation sources, while the analysis technique uses qualitative-interpretative content analysis. By introducing the three collectors’ works, examining Ibnu Al-Qayyim’s interpretation in them, and comparing the three, both in terms, of similarities and differences; It can be concluded that Ibnu Al-Qayyim really proved himself as a commentator who used many thematic interpretation methods (maudhu’i) in his various works. The results of the research in this article also provide implivation for the feasibility of Ibnu Al-Qayyim’s thematic interpretation as an object of scientific research, including through his three collector’s books.